2017
DOI: 10.3758/s13415-017-0504-1
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotion impedes emotional but not cognitive conflict processing

Abstract: Cognitive control enables successful goal-directed behavior by resolving a conflict between opposing action tendencies, while emotional control arises as a consequence of emotional conflict processing such as in irony. While negative emotion facilitates both cognitive and emotional conflict processing, it is unclear how emotional conflict processing is affected by positive emotion (e.g., humor). In 2 EEG experiments, we investigated the role of positive audiovisual target stimuli in cognitive and emotional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 64 publications
(120 reference statements)
4
40
2
Order By: Relevance
“…The participants’ emotional state did not influence the exogenous attention process associated with this component, which may also reflect an advantage from an evolutionary perspective; thus, the fact that emotional, potentially relevant distractors are attended independently of the current mood state at early attentional stages (when distractors have not been consciously processed yet) seems an adaptive and life-sustaining mechanism. It should be mentioned at this point that some previous studies employing other ‒non-CDTD‒ paradigms reported increased amplitudes at early latencies only in response to negative relative to neutral task-irrelevant stimuli 71 , while task-irrelevant positive compared to neutral stimuli resulted in a reduction of N1 and N2 in an identical paradigm 72 . Therefore, the advantage of positive stimulation must be understood as closely linked to experimental demands.…”
Section: Discussionmentioning
confidence: 85%
“…The participants’ emotional state did not influence the exogenous attention process associated with this component, which may also reflect an advantage from an evolutionary perspective; thus, the fact that emotional, potentially relevant distractors are attended independently of the current mood state at early attentional stages (when distractors have not been consciously processed yet) seems an adaptive and life-sustaining mechanism. It should be mentioned at this point that some previous studies employing other ‒non-CDTD‒ paradigms reported increased amplitudes at early latencies only in response to negative relative to neutral task-irrelevant stimuli 71 , while task-irrelevant positive compared to neutral stimuli resulted in a reduction of N1 and N2 in an identical paradigm 72 . Therefore, the advantage of positive stimulation must be understood as closely linked to experimental demands.…”
Section: Discussionmentioning
confidence: 85%
“…For each time window a repeated-measures ANOVA was calculated, using emotion (emotional, neutral), congruence (congruent, incongruent), region (anterior, posterior) and side (left, right) as within-subject factors and age (younger, older) as a between-subject factor. As videos prior to voice onset in Experiment 1 were identical (as emotion of face and voice was kept constant and only vocalization varied) no baseline correction was applied before the voice onset ( Zinchenko et al, 2015 , 2017 ). Only statistically significant main effects and interactions that involved the critical factors emotion, congruence, and group are reported in the section “Results.”…”
Section: Methodsmentioning
confidence: 99%
“…Several event-related potential (ERP) studies have shown how the affective content of speech can modulate ERP responses as early as 200 ms for auditory stimuli very short in length (e.g., Paulmann and Kotz, 2008;Paulmann et al, 2010;Paulmann and Pell, 2010;Paulmann et al, 2013;Schirmer et al, 2013;Schirmer and Kotz, 2006) and at about 300-400 ms for more complex and longer stimuli (see the review by Kotz and Paulmann, 2011). Zinchenko et al (2015Zinchenko et al ( , 2017) used an auditory processing task in dynamic multisensory stimuli and showed that negative emotions can have a modulatory effect as early as 100 ms after stimulus onset (as well as subsequently influencing P200 and N200 ERP components).…”
Section: Introductionmentioning
confidence: 99%